2021
DOI: 10.1080/09687637.2021.1932754
|View full text |Cite
|
Sign up to set email alerts
|

Rapid literature review on the impact of health messaging and product information on alcohol labelling

Abstract: Background and aim: Alcohol labelling enables people to make informed decisions about the products they purchase and consume. This rapid review explores the impact of health messaging and product information on consumer attention, comprehension, recall, judgment and behavioural compliance in relation to alcohol use. Methods: The rapid review adopted a multi-faceted search strategy to identify primary studies on health messaging and/or product information on alcohol packaging, and the impact of these on consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 94 publications
0
27
0
Order By: Relevance
“…This review aimed to examine the scope of the (quasi-)experimental research on novel and enhanced alcohol health warning labels and to identify the key characteristics of the effective warning labels. Twenty-seven papers were included, the majority of which were published in 2018 or later, indicating an uptake in interest surrounding the topic from the research community (recognised also in other broader reviews [45]). This is aligned with the increase in policy-related labelling discussions, such as in Codex Alimentarius, at the EU or national level (e.g., [77,78]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review aimed to examine the scope of the (quasi-)experimental research on novel and enhanced alcohol health warning labels and to identify the key characteristics of the effective warning labels. Twenty-seven papers were included, the majority of which were published in 2018 or later, indicating an uptake in interest surrounding the topic from the research community (recognised also in other broader reviews [45]). This is aligned with the increase in policy-related labelling discussions, such as in Codex Alimentarius, at the EU or national level (e.g., [77,78]).…”
Section: Discussionmentioning
confidence: 99%
“…There has also been increased research activity, and a number of labelling-related reviews have been published recently. Previous reviews focusing on alcohol HWL operated with a relative scarcity of studies [43], focused only on one aspect of the label (image vs. text) [44] or made a brief narrative overview of health labelling studies as part of broader alcohol labelling [45]. Whilst our work partially overlaps with other reviews in examining the impact of labels, our review adds a thorough and systematic examination of the scope of (quasi-)experimental research on new or enhanced health warning labels, including an overview of the labels used in the studies and the explanatory variables studied.…”
Section: Introductionmentioning
confidence: 99%
“…This is unsurprising considering alcohol packaging in the UK is not designed to meaningfully engage or inform consumers, with ambiguous messaging in small fonts usually positioned on the back of packs and over 70% of labels not including up‐to‐date low‐risk drinking guidelines [8,11,12]. Salient warnings with specific health‐related messages, as used in our study, can positively influence consumer attention, comprehension, recall, judgement and behavioural compliance [3]. The lack of exposure to warnings on alcohol packaging may help to explain why we failed to find significant differences between pictorial and text warnings in terms of perceived cognitive and behavioural response, in direct contrast to the vast majority of studies in the tobacco field [45].…”
Section: Discussionmentioning
confidence: 99%
“…There is clearly a need to do so given that alcohol misuse is a key risk factor for illness, disability and death, implicated in more than 200 diseases and responsible for approximately 3.3 million deaths annually [1]. Although academic interest in warnings on alcohol packaging is in its infancy when compared to tobacco, evidence suggests that well-designed warnings on alcohol products can capture attention, inform consumers of possible risks, increase awareness and knowledge of harms, decrease speed of drinking and support a reduction in consumption, with moderate consumer support for warnings [2][3][4][5][6][7]. Research in the United Kingdom (UK) with young adult drinkers, for instance, found that large, pictorial (image-and-text), front-of-pack warnings with specific health conditions could help reduce individual and social appeal of alcohol products [8].…”
Section: Introductionmentioning
confidence: 99%
“…Safety labels should also clearly communicate alcohol-related health risks, especially during pregnancy [60]. Large and colorful safety labels, safety labels on plain packaging, and messages on the negative outcomes of consuming alcohol are additional strategies that can attract attention, as outlined in a rapid review in 2021 [61].…”
Section: Design Of Safety Labels On Alcohol Products In and Outside O...mentioning
confidence: 99%